The Relationship Between Accounting Information Systems and Financial Performancesho - Ahmed Kadhim Sendw (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2026)
The study aimed to identify the role of accounting information systems (AIS) and how to rely on them to improve financial performance (FP). It also aimed to identify the importance of AIS in making decisions related to FP. Through the theoretical aspect, the nature of AIS, their objectives and importance in FP were discussed. The factors affecting FP were also addressed. A number of conclusions were reached, the most important of which is that there is a positive impact on the FP of the Diwaniyah Investment Authority due to its use of AIS. Also, keeping up with technological development in AIS is necessary to improve FP